Fibrinogen Caracas V, an Abnormal Fibrinogen with an Aα 532 Ser→Cys Substitution Associated with Thrombosis - Marchi, Rita; Lundberg, Ulf; Grimbergen, Jos; Koopman, Jaap; Torres, Argimiro; de Bosch, Norma B.; Haverkate, Frits; Piñango, Carmen Luisa Arocha (Thrombosis and Haemostasis, 2000)
A new dysfibrinogenemia associated with thrombophilia has been identified in a Venezuelan kindred. Thrombin and Reptilase times were prolonged and the accelerating capacity of the patient’s fibrin on the t-PA-induced plasminogen activation was decreased. In addition the affinity of fibrinogen for plasminogen was diminished. Permeability and electron microscopy studies revealed that the abnormal clot was made up of thin and densely packed fibres giving rise to a reduced fibrin gel porosity. This was confirmed by turbidity studies showing a decreased fibre mass/length ratio. Affected members were heterozygous for an Aα 532 Ser→ Cys mutation as demonstrated by genetic analyses. This abnormal fibrinogen has been designated as Fibrinogen Caracas V. The family study showed a convincing association between the mutation and thrombotic manifestations. The thrombotic tendency may be ascribed to lack of accelerating capacity of fibrin to induce fibrinolysis caused by an abnormal clot structure with thin fibres and reduced porosity.
Keywords: Dysfibrinogenemia; thrombophilia; thrombosis